The Influence of Using Empirical Equations in order to Determine CBR in Flexible Pavement Design. Case Study: Bogotá D.C. - Hugo Alexander Rondón-Quintana, Carlos Alfonso Zafra-Mejía, Juan Pablo Rodríguez-Miranda (International Journal of Advanced Science and Technology, 2020)
One of the main design variables in flexible pavement design is the subgrade. Generally, this variable is characterized in design methods through the resilient modulus (Mr). However, in most cases, in many countries, Mr is estimated through empirical equations that are correlated to CBR (Californian Bearing Ratio), which in turn are obtained with other equations that correlate it to the dynamic penetration index (DPI). This study evaluated if said equations can be used with reliability in the design of flexible pavements in the city of Bogotá D.C. (Colombia). Additionally, there was an analysis of the possible influence produced by the use of these equations in the design of flexible pavement structures. A general conclusion obtained was that by using empirical equations, it is possible to design flexible pavement with inadequate thickness (undersizing), given that CBRs obtained when using them tend to be higher than those obtained directly on the field. Keywords: Californian Bearing Ratio, CBR, dynamic penetration index, DPI, dynamic cone penetration, flexible pavement design.